Origen’s and Plato’s Poetical Aspirations - Kačerauskas, Tomas (Problemos, 2000)
What is the relationship between poetry and philosophy? Does the ancient Greeks opposition between philosophy and poetry mean that there is an insuperable gap between the two? Using Origen’s and Plato’s texts, the author shows that such gap is impossible. He also gives a sketch of philosophical poetics through the practice of interpretation. Origen uses poetic methods to interpret Holy Scripture, which he considers to be poetic Writ. Therefore he needs a special poetic method to understand it. Origen's ethics, cosmology and epistemology arc all linked with poetics. Christ is Logos, being both alive and reasonable Word. This is the word of creation, explanation, demonstration and promise. As the Scripture is unified with poetic harmony so the whole world is linked with this holy Word. Plato in “Pheadrus” is intentionally poetic. Pure logic is unbelievable because it has no intrigue, rhythm or play of irony. The madness expresses Plato's poetics. The madness coincides with poetic inspiration. Madness as such is a principle of poetics, not of aesthetics. Dialectics is both the concentration and the distribution for Plato. The poetic aspect of madness concentrates the entire dialogue. Distribution supposes a pluralistic (poetic) method. Hence philosophical poetics consists of science, dialectics and poetry. It is (1) poetic reasoning and (2) interpretation; (3) its themes arc not only poetry or art; (4) rather it is a mastery of harmony of play and dialectics.